Corrigendum: Development of Marine Ecotourism in Indonesia: Case of Maligi Nature Reserve, Province of West Sumatra (2021 IOP Conf. Ser.: Earth Environ. Sci. 695 012029). Issue 1 (March 2021) - Zamzami, L.; Azwar,; Ermayanti,; Hendrawati,
Abstract: Please see Article PDF for corrigendum text.